Crystal structures and mesomorphic properties of Schiff base homologs and derivatives, and magnetic properties of their dimeric and dinuclear copper(II) complexes - Abdullah, N.; Halid, Y.Y.; Tee, J.T.; Azil, Afiq (Taylor & Francis, 2016)
Three N2O4 Schiff. base homologs, H2L1 (n = 8), H2L3 ((n = 9), and H2L4 (n = 10) were obtained from the reactions of 2-HOC6H4CHO with H2N(CH2)8-10NH2, while a derivative of H2L1, namely, H2L2, was obtained from the reaction of 3,5-X2-2-HOC6H2CHO (X = tert-butyl) with H2N(CH2)8NH2. The Schiff bases H2L2 (triclinic; P-1), H2L3 (monoclinic; C2/c), and H2L4 (monoclinic; P21/c) were single crystals with low melting temperatures (less than 100°C). The homologs exhibited mesomorphisms, while the derivative was not mesomorphic and did not reform crystals from its melt. Copper(II) complexes of H2L1, H2L2 and H2L4 were dimeric, while that of H2L3 was dinuclear with chelating CH3COO ligand. These complexes were paramagnetic with insignificant interactions between the copper(II) atoms and have high decomposition temperatures (Tdec = 268-304°C). Their melting temperatures (Tmelt = 138.9-190.2°C) were higher than the corresponding Schiff bases, but they were not mesomorphic.